The relationship between employees' adaptability, employees' judgment toward the benefit of the organization merger and organizational commitment / Laila Meiliyandrie Indah Wardani and Okina Fitriani - Indah Wardani, Laila Meiliyandrie; Fitriani, Okina (2010)
The main objective of this research was to examine the relationship between employees' adaptability, employees' judgment towards the benefit of the organization merger and organizational commitment. The subject of the study consisted of 209 employees of the oil company in Jakarta, Indonesia. Data was collected using a set of questionnaires which covered the understanding of the employees' adaptability, the employee's judgment towards the benefit of the merger, the Organizational Commitment Questionnaire and subject's demographic information. The result of the study suggests that there were significant effect of the employees' adaptability and social judgment towards the organizational merger with the organizational commitment. The effect was proven to exist both individually and in combination. The adaptability provided 10.4 percent effect to estimate organizational commitment while the social judgment gives more significant effect, i.e. 42.4 percent. The study has also indicated there was an explicit positive relationship between the employees' adaptability and the employees' social judgment towards the benefit of organizational merger. The employees' judgment of the benefit of the merger was found to be different depends on the origin where they were work, either acquirer company or acquired company. However, there was no difference in the employees' commitment to the merged company from both original companies. The validity and reliability of the three psychometric tools that have been used in this study was considered adequate to measure the employees' adaptability, social judgment towards the benefit of he merger and the organizational commitment.